Summary of 1990 Supreme Court rulings, July to December 1990 - Martinez, Daniel T. (Manila Central Book Supply, Inc., 1991)
Part I : Political law -- Labor and social legislation -- Civil law -- Taxation -- Mercantile law -- Criminal law.
Keywords: Law reports, digests, etc. -- Philippines